Selenium toxicity to survival and reproduction of Collembola and Enchytraeids in a sandy loam soil. (4th January 2018) - Kuperman, Roman G.; Checkai, Ronald T.; Simini, Michael; Phillips, Carlton T.; Higashi, Richard M.; Fan, Teresa W.‐M.; Sappington, Keith
Abstract: We investigated the toxicity of selenium (Se) to the soil invertebrates Folsomia candida (Collembola) and Enchytraeus crypticus (potworm). Studies were designed to generate ecotoxicological benchmarks for developing ecological soil screening levels (Eco‐SSLs) for risk assessments of contaminated soils. For the present studies, we selected Sassafras sandy loam, an aerobic upland soil with soil characteristics (low levels of clay and organic matter, soil pH adjusted from 5.2 to 7.1) that support high relative bioavailability of the anionic Se species that is typically found in aerobic soil. The Se was amended into soil as sodium selenate, subjected to weathering and aging using 21 d of alternating cycles of air‐drying/rehydration to 60% of the water‐holding capacity of the Sassafras sandy loam soil, under ambient greenhouse conditions. Effective concentrations at 20 and 50% (EC20 and EC50) levels for production of juveniles (reproduction) were 4.7 and 10.9 mg of Se/kg of soil (dry mass basis), respectively, for Collembola, and 4.4 and 6.2 mg/kg, respectively, for the potworms. The data enabled the derivation of toxicity benchmarks, contributing to the development of a soil invertebrate‐based Eco‐SSL of 4.1 mg/kg for Se. Environ Toxicol Chem 2018;37:846–853. Published 2017 Wiley Periodicals Inc. on behalf of SETAC. This article is a US government work and, as such, is in the public domain in the United States of America.